Мотив «кохання» у поетичній та прозовій творчості Аннетте фон Дросте-Гюльсхоф: засоби вербалізації - Білоус, Наталя Володимирівна; Белоус, Наталья Владимировна; Bilous, Natalia (My University, 2021)
UK: Метою представленого дослідження є аналіз творчого арсеналу А. фон Дросте-Гюльсхоф для розкриття теми любові у поетичних творах з різних періодів творчості майстрині та у її незавершеному романі «Bei uns zu Lande auf dem Lande». За мету також поставлено встановлення кореляції фактів особистого життя авторки і висловлень її ліричних героїв щодо романтичних стосунків та пошуку любові та взаємності у коханні. Методи. Дослідження ґрунтується на загальнонаукових методах аналізу і включає біографічний, семантико-стилістичний та порівняльний методи, лінгво-поетичну інтерпретацію, а також контекстуальний інтерпретаційний аналіз. EN: Purpose of the present research is to analyze A. Droste’s creative arsenal in revealing the theme of love in poetry of different periods of the author’s work as well as in her unfinished novel “Bei uns zu Lande auf dem Lande”. The purpose was to identify the correlation between the facts of Droste’s personal life and the statements of her lyrical heroes about romantic relationships and the search for love and mutuality in relationships. Methods. The research is based on general scientific methods of analysis and includes the use of biographical, semantic and stylistic, comparative methods, linguopoetic interpretation, as well as interpretative analysis of the context. Results. The results of the research made it possible to establish Droste’s tendency to represent two types of love relationships and to identify the means of verbalization of the concept “love”. Based on the biographical method, a correlation between the biographical facts and the perspectives in love relations of the characters of the author’s two poetic cycles has been established. The biographical nature of the male protagonist’s image in her prose work has been considered. An interpretative analysis of the mythological images and symbols in Droste’s epistles from the cycle “Gedichte vermischten Inhalt” has been performed. Conclusions. Droste’s creative palette is characterized by the richness and diversity of semantic fields of the concept “love” and the skilful use of the system of mythological images to maximize the author’s representation of the multidimensional nature of the lyrical characters’ feelings, including both their emotional reaction and critical view of life. Either in poetry or in prose, Droste highlights two categories of love relationships: love-passion and love-friendship. The study of the works from different periods of the author’s life has revealed that the above mentioned duality of love was clearly realized by Droste, and thus was represented in her literary work, both in the early periods and in the cycles of 1842-1844. The fundamental feature of representing the romantic feelings of Droste’s characters is unconditionality: the lyrical characters rely on their own past and do not hesitate to draw strength and inspiration for further personal searches and shared experiences.
Motive of “love” in the poetic and prose creative works of annette von droste-hülshoff: means of verbalization
Keywords: біографічність; система міфообразів; міфологічний символ; епістола; творча палітра; biographicality; system of mythological images; mythological symbol; epistle; creative palette